Green Economy: Navigating The Path To A Sustainable Future - Reinatto Yakobus Pati Agon Atakelan; Aprilia Tri Kurniawati; Hwihanus Hwihanus (International Journal of Economics, Commerce, and Management, 2024)
For the final ten a long time, the idea of a green economy has gotten to be progressively appealing to arrangement producers. Be that as it may, green economy covers a part of different concepts and its joins with maintainability are not continuously clear. The urgency of addressing environmental challenges has spurred the rise of the green economy, a paradigm shift towards economic growth that prioritizes environmental protection and social well-being. This article explores the green economy through the lens of accounting, highlighting the crucial role accountants play in facilitating the transition to a sustainable future. We examine the principles of green accounting, its potential benefits for environmental sustainability and economic growth, and the challenges associated with its implementation. The article concludes by emphasizing the require for adjustment inside bookkeeping instruction to prepare future bookkeepers with the aptitudes and information fundamental to explore the complexities of the green economy.